Reducing Ammonia (NH3) Levels in Fish Cage Water Using Activated Carbon Adsorbent Derived from Purple Corn Cob - Hamid, Muhammadin; Nasution, Tulus Ikhsan; Elfinita, Revi; Wijoyo, Hadi; Isnaeni, Isnaeni (Science and Technology Indonesia, 2024)
Successfully made adsorbent of activated carbon made from purple corn cob which aims to minimize ammonia (NH3) levels found in water in fish farming with cage ponds. Activated carbon using carbonization method with a change in temperature that is between 550°C, 600°C, and 650°C and activation using Na2CO3 solution as activator. Activated carbon that has been obtained has exceeded the standard of SNI No.06-3730-1995, with characteristics including carbon yield ranging from 79.71% to 89.85%, moisture content ranging from 11.3% to 25.4%, volatile matter content ranging from 10.10% to 24.5%, ash content ranging from 9.7% to 9.9%, and fixed carbon content ranging from 65.7% to 79.7%. Then test results were obtained such as CO2 functional groups were found to enhance the adsorption process. Activated carbon displays the presence of a predominantly amorphous structure but also revealed a crystalline carbon structure. The highest peak was obtained at 29.7° with Miller index (201). The activated carbon displays the presence of pores on the scattered surface with carbon elements dominating. Adsorption mechanism to reduce ammonia (NH3) using activated carbon due to intermolecular interaction process. So that when testing the application for ammonia absorption, the best results were obtained in the sample with an adsorbent mass of 1.50 g at a carbonization temperature of 650°C with an adsorption capacity value of 546.34 mg/g and ammonia reduction of 82%. This research can open up opportunities for the potential development of new materials, especially for fish farming through cage techniques.